Nanocomposite coatings and nanocomposite materials - Öchsner, Andreas; Ahmed, Waqar; Ali, Nasar (Materials science foundations, 2009)
Nanocomposite materials are formed by mixing two or more dissimilar materials at the nanoscale in order to control and develop new and improved structures and properties. The properties of nanocomposites depend not only upon the individual components used but also upon the morphology and the interfacial characteristics. Nanocomposite coatings and materials are among the most exciting and fastest-growing areas of research; with new materials being continually developed which often exhibit novel properties that are absent in the constituent materials. Nanocomposite materials and coatings theref.